Fluorinated phenmetrazine "legal highs" act as substrates for high-affinity monoamine transporters of the SLC6 family. (15th May 2018) - Mayer, Felix P.; Burchardt, Nadine V.; Decker, Ann M.; Partilla, John S.; Li, Yang; McLaughlin, Gavin; Kavanagh, Pierce V.; Sandtner, Walter; Blough, Bruce E.; Brandt, Simon D.; Baumann, Michael H.; Sitte, Harald H.
Abstract: A variety of new psychoactive substances (NPS) are appearing in recreational drug markets worldwide. NPS are compounds that target various receptors and transporters in the central nervous system to achieve their psychoactive effects. Chemical modifications of existing drugs can generate NPS that are not controlled by current legislation, thereby providing legal alternatives to controlled substances such as cocaine or amphetamine. Recently, 3-fluorophenmetrazine (3-FPM), a derivative of the anorectic compound phenmetrazine, appeared on the recreational drug market and adverse clinical effects have been reported. Phenmetrazine is known to elevate extracellular monoamine concentrations by an amphetamine-like mechanism. Here we tested 3-FPM and its positional isomers, 2-FPM and 4-FPM, for their abilities to interact with plasma membrane monoamine transporters for dopamine (DAT), norepinephrine (NET) and serotonin (SERT). We found that 2-, 3- and 4-FPM inhibit uptake mediated by DAT and NET in HEK293 cells with potencies comparable to cocaine (IC50 values < 2.5 μM), but display less potent effects at SERT (IC50 values >80 μM). Experiments directed at identifying transporter-mediated reverse transport revealed that FPM isomers induce efflux via DAT, NET and SERT in HEK293 cells, and this effect is augmented by the Na + /H + ionophore monensin. Each FPM evoked concentration-dependent release of monoamines from rat brain synaptosomes. Hence, this study reports for the first time the mode of action for 2-, 3- and 4-FPM and identifies these NPS as monoamine releasers with marked potency at catecholamine transporters implicated in abuse and addiction. This article is part of the Special Issue entitled 'Designer Drugs and Legal Highs.' Highlights: Fluorinated phenmetrazines target monomamine transporters. Flourinated phenmetrazines act as amphetamine-like drugs. Selectivity for catecholamine transporters indicates a high potential for addiction.